PENGARUH DEBT COVENANT, LEVERAGE, GROWTH OPPORTUNITIES DAN FINANCIAL DISTRESS TERHADAP KONSERVATISME AKUNTANSI (Studi Pada Perusahaan Sub Sektor Transportasi yang terdaftar Di Bursa Efek Indonesia BEI Periode (2017-2019) - Faizah Hardi Yanti; Zul Azmi; Muhammad Ahyaruddin (Institut Bisnis dan Teknologi Pelita Indonesia, 2022)
ABSTRACT This research aims to find out the influence of debt covenant, leverange, growth opportunities and financial distress on accounting conservatism in a sustainable and simultaneous manner on Transportation Sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2017-2019. This type of research is quantitatively used to examine a predetermined population or sample. In this study, sampling used purposive sampling techniques based on predetermined characteristics as many as 30 Transportation Sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2017-2019. The data analysis method is done with regression analysis of panel data with the help of Eviews 9. The regression model used is a random effect model using the classic assumption test of the T. F test and the R-Squared test. The results showed a partial hypothesis that debt covenants had a significant effect on accounting conservatism at a significant rate of 0.0000 < 0.05. Leverage had no significant effect on accounting conservatism with a significant rate of 0.2913 > 0.05. Growth Opportunities had no significant effect on accounting conservatism with a significant rate of 0.2457 > 0.05. Financial Distress had no significant effect on accounting conservatism with a significant rate of 0.0780 > 0.05. Simultaneous research shows that debt covenant, leverange, growth opportunities and financial distress to conservatism with Fcounted at 11.47838 with a probability of 0.000000 < 0.05. ABSTRAK Penelitian ini bertujuan untuk mengetahui pengaruh debt covenant, leverange, growth opportunities dan financial distress terhadap konservatisme akuntansi secara persial dan simultan pada perusahaan Sektor Transportasi yang terdaftar di Bursa Efek Indonesia (BEI) periode 2017-2019. Jenis penelitian ini adalah riset kuantitatif yang digunakan untuk meneliti sampel populasi atau sampel yang telah ditentukan. Sampel diambil dengan teknik purposive sampling berdasarkan karakteristik yang telah ditentukan. Data diperoleh dari 30 perusahaaan Sektor Transportasi yang terdaftar di Bursa Efek Indonesia (BEI) periode 2017-2019. Metode analisis data menggunakan analisis regresi data panel dengan bantuan Eviews 9. Hasil penelitian menunjukkan secara parsial debt covenant berpengaruh secara signifikan terhadap konservatisme akuntansi. Leverage tidak berpengaruh terhadap konservatisme akuntansi, Growth Opportunities tidak berpengaruh terhadap konservatisme akuntansi, dan Financial Distress tidak berpengaruh terhadap konservatisme akuntansi.